2017
DOI: 10.1038/s41598-017-15751-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of blood-derived microRNAs for schizophrenia: results of a meta-analysis and validation

Abstract: There is an increasing interest in searching biomarkers for schizophrenia (SZ) diagnosis, which overcomes the drawbacks inherent with the subjective diagnostic methods. MicroRNA (miRNA) fingerprints have been explored for disease diagnosis. We performed a meta-analysis to examine miRNA diagnostic value for SZ and further validated the meta-analysis results. Using following terms: schizophrenia/SZ, microRNA/miRNA, diagnosis, sensitivity and specificity, we searched databases restricted to English language and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…Predicting miRNAs binding to HTR1B, we found that starBase and RNAHybrid yielded miR-96 [12]. found that miR-21 in peripheral blood is a highly sensitive and specific biomarker for the diagnosis of schizophrenia [20]. MicroR-21 was also significantly decreased in the peripheral blood of schizophrenic patients after antipsychotic treatment [14].…”
Section: Discussionmentioning
confidence: 94%
“…Predicting miRNAs binding to HTR1B, we found that starBase and RNAHybrid yielded miR-96 [12]. found that miR-21 in peripheral blood is a highly sensitive and specific biomarker for the diagnosis of schizophrenia [20]. MicroR-21 was also significantly decreased in the peripheral blood of schizophrenic patients after antipsychotic treatment [14].…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, among the differentially expressed miRNAs, 11 could be used to dissociate schizophrenia samples from control samples with 75% to 90% accuracy (90). Despite this remarkable precision, however, blood miRNA profiling tends to produce equivocal results in the context of schizophrenia, with biomarker candidates varying across independent studies (91)(92)(93). While this variability may arise from various cofounding effects, including differences in the type of tissue, low sample size, and smoking-related epigenetic effects (94), it may also mirror the disorder's etiological (and phenotypic) heterogeneity (95,96).…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…However, the major shortcoming of using blood-based miRNA for CRC screening is the detection specificity. This is because miRNAs might arise from other cancer(s) [64,65], depression [66], and virus infection(s) [67,68]. Therefore, faecal-based miRNA detection may be an alternative option [57,59,60,69].…”
Section: Screening Tools Under Developmentmentioning
confidence: 99%